14th Asia-Pacific Software Engineering Conference (APSEC'07) 2007
DOI: 10.1109/aspec.2007.28
|View full text |Cite
|
Sign up to set email alerts
|

Deriving Software Process Simulation Model from SPEM-based Software Process Model

Abstract: It is difficult to adopt a simulation technology for simulating a software process because of the difficulty in developing a simulation model. In order to resolve the difficulty, we consider the following issues: reducing the cost to develop a simulation model, reducing the simulation model complexity, and increasing the modularity of a simulation model. We propose an approach to deriving a Discrete Event System Specification (DEVS)-Hybrid simulation model from a Software Process Engineering Metamodel (SPEM)-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…see the pairs [148] and [57], [10] and [81], as well as [149] and [59]. A methodology to develop a simulation model proposed by Park et al is reported in three articles which are very similar as well [120,35,34].…”
Section: Assessing the Evolution Of The Fieldmentioning
confidence: 90%
“…see the pairs [148] and [57], [10] and [81], as well as [149] and [59]. A methodology to develop a simulation model proposed by Park et al is reported in three articles which are very similar as well [120,35,34].…”
Section: Assessing the Evolution Of The Fieldmentioning
confidence: 90%
“…The closest work to our current research [2] proposes an approach to derive a hybrid simulation model (DES and SD) from a SPEM 1.1 process model. We consider the hybrid mechanism as an advantage when contrasted to our work.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the closest work to our current research is the work of Park et al [2]. The authors propose an approach to derive a hybrid simulation model from a process model created with SPEM.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The UML profile for SPEM gives benefits for present- ing different perspectives of a software process model using UML diagrams. We construct the process model using the use case diagram and the activity diagram (Park et al, 2007). The use case diagram describes the assignment of roles to phases or activities and represents the work breakdown structure (WBS) of a process.…”
Section: Activity a Activity Bmentioning
confidence: 99%